2011
DOI: 10.1080/07370016.2011.564070
|View full text |Cite
|
Sign up to set email alerts
|

“Step-by-Step We are Stronger”: Women's Empowerment Through Photovoice

Abstract: Photovoice, as one method of participatory action research, has been used to better understand local realities and promote health in many countries and with diverse populations. It has been especially effective as a process for women to explore health and contextual issues often related to oppression and marginalization. This article discusses the impact of a photovoice process on a small group of lone mothers carrying out a community health assessment in eastern Canada. According to the women, their level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 64 publications
3
32
0
Order By: Relevance
“…The Photovoice method of inquiry empowered participant voices and supported the development of critical knowledge to moderate and transform social injustices for older women. This empowerment, enhanced through education and learning opportunities, can improve self-identity and expose new possibilities (Duffy, 2011;Mayfield-Johnson, Rachal, & Butler, 2014). As posited by Krašovec, Golding, Findsen, and Schmidt-Hertha (2017), learning in later life is not so much concerned with the issue of aging itself but more about quality of life regardless of age.…”
Section: The Impact Of Photovoice On the Participantsmentioning
confidence: 99%
“…The Photovoice method of inquiry empowered participant voices and supported the development of critical knowledge to moderate and transform social injustices for older women. This empowerment, enhanced through education and learning opportunities, can improve self-identity and expose new possibilities (Duffy, 2011;Mayfield-Johnson, Rachal, & Butler, 2014). As posited by Krašovec, Golding, Findsen, and Schmidt-Hertha (2017), learning in later life is not so much concerned with the issue of aging itself but more about quality of life regardless of age.…”
Section: The Impact Of Photovoice On the Participantsmentioning
confidence: 99%
“…() used photovoice to engage children from low‐income families in a project designed to identify assets and issues at their school then develop action plans to manage the issues. Photovoice has been effectively used in public health initiatives to empower individuals who may not otherwise have a voice (Catalani & Minkler, ; Duffy, ; Gant et al., ). In a recently published participatory action research study, photovoice was shown to empower a small group of marginalized single mothers in Canada (Duffy, ).…”
Section: Introductionmentioning
confidence: 99%
“…Photovoice has been effectively used in public health initiatives to empower individuals who may not otherwise have a voice (Catalani & Minkler, ; Duffy, ; Gant et al., ). In a recently published participatory action research study, photovoice was shown to empower a small group of marginalized single mothers in Canada (Duffy, ). In a qualitative review of 31 studies that used photovoice, the authors strongly advocated for the use of photovoice as a vehicle for community change (Hergenrather, Rhodes, Cowan, Bardhoshi, & Pula, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Visualizing Breast Cancer (VBC) study was the first opportunity many First Nations and Métis women had to voice and image their experiences, identifying a pressing need for further research into their social location (e.g., class, geography) and role of identity (e.g., traditional beliefs and values). The pilot was also richly suggestive of the capacity for expressive methods (e.g., photography) based on models of empowerment (Duffy, 2011;Pulvirenti, Mcmillan, & Lawn, 2014;Van Uden-Kraan et al, 2008) to function in tandem with psychosocial and knowledge translation (KT) interventions for FNIM cancer survivors (Pulvirenti et al, 2014;Van UdenKraan et al, 2008).…”
Section: Pilot Workmentioning
confidence: 99%